Simulating hydrological connectivity and water age within a coastal deltaic floodplain of the Mississippi River Delta. (30th October 2020) - Christensen, Alexandra; Twilley, Robert R.; Willson, Clinton S.; Castañeda-Moya, Edward
Abstract: Located at the mouth of large rivers, coastal deltaic floodplains are important ecosystems for trapping sediment and removing excess nitrogen introduced to the river through agricultural and urban runoff. Hydrological connectivity (the percent of river channel water interacting with floodplain wetlands), water age (the time elapsed since water entered the system via the main river channel) and water temperature have strong impacts on the biogeochemical processes controlling the fate of sediment and nutrients at continental margins. A Delft3D hydrodynamic model was used to explore the role of river and tide forcings, hydrogeomorphology, and vegetation roughness on hydrological connectivity, water age, and water temperature of a young, prograding river delta in coastal Louisiana, Wax Lake Delta. Across a simulation period of January to June 2015, an average of 39.9% of river flow entered the delta floodplains and water within the floodplains had an average water age of 0.8 days. In winter and spring, floodplain zones with higher sediment surface elevations (supratidal hydrogeomorphic zones) were characterized by increased water age and warmer water temperatures compared to subtidal floodplains and channels. Our experimental models indicate that the presence of wetland vegetation decreases hydrological connectivity by preventing flow of water into deltaic floodplain, but increases water age by retaining water within the floodplains. Despite small amplitudes ( 30 cm), tides create hourly exchange between channels and floodplains, which decreases water age in floodplains, but has little impact on average connectivity. Our results emphasize the role of both hydrological forcings (river and tides) and ecosystem features (vegetation and sediment surface elevation) in regulating channel-floodplain interactions in deltaic systems. Evaluated against field data, which is often difficult to collect at high spatial and temporal frequency in floodplains, this model performs well, highlighting the utility of numerical models in capturing landscape-scale hydrodynamics. Graphical abstract: Image 1 Highlights: Hydrogeomorphic zones in coastal deltaic floodplains exhibit hydrologic differences. Warmest temperatures and oldest water age in supratidal and intertidal floodplains. River stage, tides, and vegetation roughness control channel-floodplain exchange. Channel-floodplain connectivity increases from the delta apex to the delta front.